ANALISIS KESESUAIAN PENGUSAHAAN AIR TANAH OLEH PT. TIRTA INVESTAMA DI KABUPATEN BOGOR BERDASARKAN PERATURAN TENTANG SUMBER DAYA AIR: Analysis of the Compliance of Groundwater Extraction Permits by PT. Tirta Investama in Bogor Regency Based on Water Resource Regulations - Bagas Arya Putra; Sri Untari Indah Artati (Reformasi Hukum Trisakti, 2025)
Water has an important role as a basic human need as regulated in Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Provisions regarding water are regulated through Law Number 17 of 2019. The formulation of the problem is to examine the suitability of the Groundwater Business Permit held by PT. Tirta Investama in Bogor Regency. This study uses a normative juridical approach with a descriptive method based on secondary data, including a study of Law No. 17 of 2019 concerning Water Resources. The analysis was carried out qualitatively, with deductive conclusions drawn. The results of the study indicate that the Groundwater Business Permit held by PT. Tirta Investama is in accordance with applicable regulations regarding the Standards for Implementing Groundwater Extraction Permits.